Cellular and oxidative stress responses of Mytilus galloprovincialis to chlorpromazine: implications of an antipsychotic drug exposure study - Impellitteri, Federica; Yunko, Kateryna; Martyniuk, Viktoria; Khoma, Vira; Piccione, Giuseppe; Stoliar, Oksana; Faggio, Caterina (Frontiers in Physiology, 2023)
Bivalve molluscs like Mytilus galloprovincialis are valuable bioindicators due to their filter-feeding lifestyle, wide distribution, and ability to concentrate xenobiotics. Studying the effects of pharmaceuticals on these molluscs is crucial given their presence in surface waters. This study investigated the response of M. galloprovincialis to chlorpromazine (Cpz), an antipsychotic with antiviral activity against influenza, HIV, and coronaviruses in human cells. In this study, we examined the 14-day impact of chlorpromazine (Cpz) on the model species M. galloprovincialis at two concentrations (Cpz 1: 12 ng L-1 or 37 pM; Cpz 2: 12 µg L-1 or 37 nM). To ensure controlled exposure, a stock solution of Cpz was prepared and introduced into the tanks to match the intended concentrations. Seawater and stock solutions were refreshed every 48 hours. The primary focus of this study centered on evaluating cell viability, cell volume regulation, and oxidative stress indicators.Although cell volume regulation, as assessed by decreasing regulatory volume (RVD), did not show statistically significant changes during the experiment, digestive cell viability, on the other hand, showed a significant decrease (p<0.01) in the Cpz 2 group, suggesting effects on the general health and survival of these cells. Biochemically, in both Cpz 1 and Cpz 2, superoxide dismutase (SOD) activity increased, while catalase (CAT) decreased, causing an elevated lipid peroxidation (TBARS) and protein carbonylation (PC), particularly in the Cpz 2 group. The level of reduced glutathione (GSH) increased in both exposures, whereas the level of GSSG increased only in the Cpz 1 group. Consequently, the GSH/GSSG ratio was elevated in the Cpz 2 group only. A comparison of the magnitudes of anti-and pro-oxidative manifestations indicated a pro-oxidative shift in both exposures. These findings show that Cpz induces non-specific symptoms of biochemical and cellular disturbances in M. galloprovincialis even at the low picomolar concentration.